eSNaPD: a versatile, web-based bioinformatics platform for surveying and mining natural product biosynthetic diversity from metagenomes - Reddy, Boojala Vijay B. (2014)
eSNaPD (environmental Surveyor of Natural Product Diversity) is a web-based bioinformatics and data aggregation platform that aids in the discovery of gene clusters encoding both novel natural products and new congeners of medicinally relevant natural products using (meta)genomic sequence data. Using PCR generated sequence tags, the eSNaPD data analysis pipeline profiles biosynthetic diversity hidden within (meta)genomes by comparing sequence tags to a reference dataset of characterized gene clusters. Sample mapping, molecule discovery, library mapping and new clade visualization modules facilitate the interrogation of large (meta)genomic sequence datasets for diverse downstream analyses, including, but not limited to, the identification of environments rich in untapped biosynthetic diversity, targeted molecule discovery efforts and chemical ecology studies. eSNaPD is designed to generate a global atlas of biosynthetic diversity that can facilitate a systematic, sequence-based interrogation of nature’s biosynthetic potential.